(untitled) (Szociológiai Szemle, 2024)
The changes of income, employment, satisfaction and anomie in Hungary and East Germany since the regime change are analysed on the basis of the household income panel surveys of the two countries and other surveys. Data from West Germany are presented for comparison. The transition followed a rather different path in Hungary and East Germany. The average real per capita income increased in East Germany and declined in Hungary. Income inequality increased in Hungary and attains more or less the level observed in West Germany, but remained more or less stable at the much lower level in East Germany. Unemployment increased to a higher level in East Germany than in Hungary. The level of dissatisfaction with personal income is higher in Hungary than in East Germany. Indicators of psychological anxiety and of anomie do not support the hypothesis of higher anxiety and anomie in Hungary. It is concluded that in Hungary the transition was dominated more by economic imperatives and in East Germany more by political imperatives, i.e. by the goal of maintaining the legitimation of the direction of the transition toward market economy and political democracy. Hungary had no other choice than to permit the economic imperatives prevail, while the massive help from West Germany permitted to mitigate the impact of economic imperatives in East Germany. In spite of these differences the legitimation of the market economy and of democracy does not seem to undermined in Hungary.